Permethrin-associated kdr Mutations through Molecular Analysis of Human Head Lice (Phthiraptera: Pediculidae) Populations in School Children in the South of Iran - Saeedeh Ebrahimi; Marzieh Shahriari-Namadi; Saeed Shahabi; Mohammad Djaefar Moemenbellah-Fard; Hamzeh Alipour (Shiraz University of Medical Sciences, 2021)
Background:Human head lice is one of the most invincible neglected skin diseases. The use of pyrethroid insecticides is a standard method of treating the disease, which leads to lice population resistance in the long run. The main aim of the current survey was to screen the biomarkers of permethrin-associated kdr (knockdown resistance) point mutations through molecular analysis of the human head lice populations in primary school children in the south of Iran.   Methods: In an experimental study, Field-collected head lice from infested students were fixed in ethanol, identified using valid taxonomic keys, and processed by PCR for kdr mutant studies. Sequencing partial voltage-sensitive sodium channel gene in different head lice populations was subsequently implemented and compared with the permethrin-resistant diamondback moth, Plutella xylostella (Lepidoptera: Plutellidae) as the gold standard.   Results:Human head lice appeared to reflect kdr point mutations in specimens from the city of Shiraz. At least three amino acid mutations at designated sites of D820E, L840F, and N874G, corresponding to replacements of aspartic acid to glutamic acid, leucine to phenylalanine, and asparagine to glycine, are clear in this representative population, respectively. At the same time, only L840F is reported as a new mutant in this survey.   Conclusion: The ongoing treatment of head lice infested in school children harboring kdr-mutated or permethrin-resistant mutants in Shiraz is risky, illogical, and contrary to the One Health initiative of the World Health Organization. Health executives should thus immediately take the indispensable steps to prohibit further procurement of permethrin.